2021
DOI: 10.3390/ijms22062825
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Cardiomyocyte Models of Brugada Syndrome—Achievements, Challenges and Future Perspectives

Abstract: Brugada syndrome (BrS) is an inherited cardiac arrhythmia that predisposes to ventricular fibrillation and sudden cardiac death. It originates from oligogenic alterations that affect cardiac ion channels or their accessory proteins. The main hurdle for the study of the functional effects of those variants is the need for a specific model that mimics the complex environment of human cardiomyocytes. Traditionally, animal models or transient heterologous expression systems are applied for electrophysiological inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 131 publications
(262 reference statements)
0
8
0
Order By: Relevance
“…Functional studies of SCN5A variants found in case 8 (p.Trp1345_Ser1349delinsPhe/p.Pro1730Leu) and in case 13 (p.Asp1741Glyfs*48/ p.Val240Met), both individually and in co-expression, are pending, as are functional studies of three of the missense variants here identified (p.Arg811Cys; p.Pro1730Leu, p.Ala1778Asp). While these models have a number of shortcomings, as they do not closely reproduce human heart physiology and clinical manifestations [ 45 , 46 ], functional and pharmacological studies in induced pluripotent cell (iPSC)-derived cardiomyocytes have overcome several of these shortcomings and have become a promising option for precision medicine [ 47 ]. These functional studies, together with careful and detailed clinical characterization of patients and apparently asymptomatic mutation carriers, are crucial to understand the complexities of SCN5A channelopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies of SCN5A variants found in case 8 (p.Trp1345_Ser1349delinsPhe/p.Pro1730Leu) and in case 13 (p.Asp1741Glyfs*48/ p.Val240Met), both individually and in co-expression, are pending, as are functional studies of three of the missense variants here identified (p.Arg811Cys; p.Pro1730Leu, p.Ala1778Asp). While these models have a number of shortcomings, as they do not closely reproduce human heart physiology and clinical manifestations [ 45 , 46 ], functional and pharmacological studies in induced pluripotent cell (iPSC)-derived cardiomyocytes have overcome several of these shortcomings and have become a promising option for precision medicine [ 47 ]. These functional studies, together with careful and detailed clinical characterization of patients and apparently asymptomatic mutation carriers, are crucial to understand the complexities of SCN5A channelopathies.…”
Section: Discussionmentioning
confidence: 99%
“…A main limitation of our investigation is the use of the HEK293 cell model ( 22 ). This cell type displays significant differences from ventricular cardiomyocytes, given that human cardiomyocytes are highlighted by their high level of differentiation and exclusive expression of certain types of ion channels and cellular structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of autologous cells that can differentiate into all cell types directly from patients has allowed the possibility of investigating the aetiology of BrS directly on patients’ cardiomyocytes without the need for invasive biopsies to obtain primary cells. These cells provide a sufficient amount of biological material that can be sustained in vitro for a long time, with a more complex and physiological expression profile compared to that of immortalised cell lines and free of species-to-species differences inherent in animal-derived models [ 60 ]. Davis and colleagues were among the pioneers in the adoption of iPSC technology for the study of BrS.…”
Section: Brugada Syndrome Experimental Modelsmentioning
confidence: 99%